Effectiveness survivors pension scheme offered by SOCSO / Siti Nur Alia Yahya - Yahya, Siti Nur Alia (2011)
This research is focusing on the “Effectiveness of Survivor’s Pension Scheme offered by SOCSO”. The researcher want to know whether the people aware or not about SOCSO and the scheme especially survivor’s pension scheme. There are three objectives in order to determine whether the people aware or not. The objectives are to study the awareness level among employee toward survivors pension scheme, to determine the information that advertised by SOCSO is enough or not and to determine the attitude of employer toward survivors pension scheme. The researcher has been distributed 50 questionnaires to the respondents. The result of the questionnaire has been analyzed and interprets with tables using method reliability test, frequency and descriptive analysis. The researcher also had come out with the recommendation. The recommendation that researcher take can help SOCSO to increase their performance for the future use that can increase effectiveness survivor’s pension scheme.